Listening criminologically: on the materiality and relationality of sound - Young, Alison (Criminological encounters, 2023)
Criminology has recently seen growing engagement with the sensory landscape as an interpretive terrain. Following the recent acoustic turn in legal studies and political theory, criminology has been grappling with some of the complexities of sound, often as part of a broader effort to analyse the sensory landscape as an interpretive terrain (McClanahan & South, 2020, 9). But as Lee notes in his ‘challenge to criminology’ (2022, p. 3), there is a need for criminologists to engage more deeply with sound, investigating what Russell and Carlton (2020) have termed ‘acoustemologies’ by which sound produces knowledge, affect, and experience. This article carries out an investigation into sound as a key aspect of criminology’s ‘sensorium’ (Herrity, Schmidt & Warr, 2021) in order to consider what is involved when we listen criminologically.